Correlation of Private and Public Legal Interests as Theoretical and Scientific and Practical Problem of Modern Law - SHATKOVSKAYA, Tatiana V.; EPIFANOVA, Tatiana V. (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The article reveals the essence of the institute of legal interest in the context of the problem of the subjective in law. Harmonization of private and public interest is considered by the author as the main target of statutory regulation. The main purpose of this study is to identify the essential features of the legal interest to ensure the harmonization of private and public interests. In order to substantiate the theory of legal interests, the authors expand the field of research activity by engaging the data of sociological, political, economic, and historical character, as well as active use of empirical method and the method of social reconstruction. The authors managed to identify the specifics of legal interest. The article suggests certain ways of realization of private interests, society interests, and state interests. The authors argue that cooperation of legal entities must be carried out in the form of a dialogue with minimal interference of the authorities into privacy. The author believes that it is impossible to exclude government interference into private interests, since it is the state, represented by the relevant authorities, that provides legal protection for the interests of individuals in the private spheres of social life. At the same time, harmonization of private and public interests in law is impossible without use of self-regulation abilities of subjects of public relations. Differentiation involves the emergence of the collective interests of destructive social conflicts, so the role of institutions in promotion of development of social compromises will increase.